Prediksi Posisi Optimal Pemain Sepakbola berdasarkan Aspek Kepribadian Tim PON Sepak Bola Putra Jawa Timur - Hariadi Said (Transbahasa, 2025)
Player position placement in football has traditionally been determined primarily by technical and physical considerations, without taking into account the personality traits inherent in each individual. This study aims to analyze the relationship between personality aspects and the suitability of playing positions (forward, midfielder, defender, and goalkeeper) in the East Java Men's PON football team. The method used is a descriptive quantitative approach with a personality questionnaire that has been tested for validity and reliability (α = 0.869). The sample was purposively selected from all core players of the East Java PON team. The results of the study show that the forward position had the highest suitability score (29.40; mean 3.67), particularly in indicators such as self-confidence, determination, and teamwork ability. Conversely, the goalkeeper position had the lowest score (24.00; mean 3.00), especially in aspects of self-confidence and communication. The midfielder and defender positions occupied middle-range scores, with strengths in play vision, communication, and tactical discipline. These findings support the theory that personality significantly influences role effectiveness within a team and reinforce sport psychology literature on the importance of a holistic approach in team selection and formation. The study recommends that coaches and team management implement a psychology-based player selection model to optimize team synergy and on-field performance. This research also opens opportunities for further studies on personality-based training interventions to enhance the specific roles of each position.